Three Different Methods of Expression Profile Analysis in Plants - Salmi, Mari L; Bushart, Thomas J; Clark, Greg B (Plant Tissue Culture and Biotechnology, 2008)
In the last 15 years many advances have been made in techniques available to molecular biologists. In the field of gene expression in particular, several new methods have become common use for determining changes in gene expression over the course of plant development, changes induced by external stimulus, and differences in the various tissue types of a plant. Here we describe the theory, general methods, and some applications for three of these new techniques in the broad field of plant biology DNA microarray, quantitative real-time reverse transcription PCR, and serial analysis of gene expression. DOI = 10.3329/ptcb.v16i1.1107 Plant Tissue Cult. & Biotech. 16(1): 63-76, 2006 (June)